PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN, HARGA, FAKTOR EMOSIONAL, BIAYA DAN KEMUDAHAN TERHADAP KEPUASAN BELANJA BUSANA SECARA DARING - Debby Arisandi; Aan Shar; Rizky Hariyadi (KOMPLEKSITAS: JURNAL ILMIAH MANAJEMEN, ORGANISASI DAN BISNIS, 2021)
This study aims to determine the effect of product quality, service quality, price, emotional factors, cost, and convenience on online fashion shopping satisfaction. This type of research is quantitative associative, the data collection technique is done using a closed questionnaire. The research was conducted in the Selebar District of Bengkulu City. The subjects in this study were 130 women ranging from 20 to 40 years who made online fashion shopping transactions. The results showed that cost and convenience as well as emotional factors had a positive and significant impact on online fashion shopping satisfaction. Meanwhile, product quality, price, and service quality do not affect online fashion shopping satisfaction